DAMPAK KEBIJAKAN TAMBAHAN PENGHASILAN PEGAWAI TERHADAP PERUBAHAN MINDSET DAN CULTURAL SET PNS BADAN KEPEGAWAIAN DAERAH PROVINSI RIAU TAHUN 2022 - Hanrimansah, Muhammad Bayu; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to examine the impact of the additional employee income policy on changes in the mindset and cultural set of Civil Servants (PNS) in the Riau Province Regional Civil Service Agency in 2022. The additional employee income policy is one of the government's efforts to improve the welfare of Civil Servants (PNS) and it is hoped that it can bring positive changes in their way of thinking (mindset) and work culture (cultural set). The research method uses qualitative methods with a descriptive approach. The type of research data is in the form of primary data obtained from research informants and secondary data obtained from documents relevant to the research topic. Then, the research location was carried out at the Riau Province Regional Civil Service Agency Office. This research found that the additional employee income policy had a significant impact on changes in mindset, especially in terms of work motivation and perceptions of work values. However, the impact on cultural set is more varied and not as strong as the impact on mindset. Several aspects of the cultural set such as teamwork, discipline, integrity and innovation show positive changes, but other aspects such as resistance to change still require further attention. Increasing income not only increases work motivation, but also encourages Civil Servants (PNS) to be more innovative, responsive and responsible in carrying out their duties. The recommendation given is that the government continues to evaluate and adjust this policy to ensure the continuation of its positive impact and pay attention to other aspects that can support increasing the performance and professionalism of Civil Servants (PNS). Keywords: Mindset, Cultural Set (Work Culture), Master Becomes Servant, Role and Authority, Outcome-Oriented (Outcome Based), Performance Management.